Consumer Price Perception on Buying Interest Xiaomi Smartphone Products - Eksananda, Annisa Aurelia; Wisandiko, Firman Adhar; Saif, Muhammad; Abdullah, Furqan; Indarwati, Tias Andarini (CV ODIS, 2021)
The purpose of the study is to analyze and explain the effect of price perception on consumer buying interest in Xiaomi smartphone products. Type of research is conclusive research design. The conclusive aims to test hypotheses and test specific relationships. Population and sample in this research consisted of 58 respondents. The data were collected by a questionnaire that was distributed to respondents online and a literature review. The analysis method was using multiple linear regression analysis by SPSS version 26. The result of this research analysis are: (1) the Perception of consumer prices has a positive and significant effect on consumer buying interest in Xiaomi products. (2) There are differences in price perceptions and buying interest in Xiaomi product. (3) The price of Xiaomi products that most consumers want is in the range of Rp. 2,000,000- Rp. 2,999,000. (4) Only 25% of Xiaomi products are in the price range desired by consumers (5) The price perception felt by consumers for Xiaomi products has a fairly high value, which means that the prices offered are currently well accepted by the public. (6) Companies to revised the prices that have been set based on what consumers want to be followed by improvements in features, benefits, and quality but still consider the company’s resources.